Current Insights and Latest Updates in Sperm Motility and Associated Applications in Assisted Reproduction - Dcunha, Reyon (Reprod Sci, 2020)
Spermatozoon is a motile cell with a special ability to travel through the woman’s reproductive tract and fertilize an oocyte. To reach and penetrate the oocyte, spermatozoa should possess progressive motility. Therefore, motility is an important parameter during both natural and assisted conception. The global trend of progressive reduction in the number and motility of healthy spermatozoa in the ejaculate is associated with increased risk of infertility. Therefore, developing approaches for maintaining or enhancing human sperm motility has been an important area of investigation. In this review we discuss the physiology of sperm, molecular pathways regulating sperm motility, risk factors affecting sperm motility, and the role of sperm motility in fertility outcomes. In addition, we discuss various pharmacological agents and biomolecules that can enhance sperm motility in vitro and in vivo conditions to improve assisted reproductive technology (ART) outcomes. This article opens dialogs to help toxicologists, clinicians, andrologists, and embryologists in understanding the mechanism of factors influencing sperm motility and various management strategies to improve treatment outcomes.